2017
DOI: 10.1088/1361-6668/aa7f68
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic granularity in pulsed laser deposited YBCO films on technical templates at 5 K

Abstract: The manifestation of granularity in the superconducting properties of pulsed laser deposited YBCO films on commercially available metallic templates was investigated by scanning Hall probe microscopy at 5 K and was related to local orientation mapping of the YBCO layer. The YBCO films on stainless steel templates with a textured buffer layer of yttrium stabilized ZrO2 grown by alternating beam assisted deposition have a mean grain size of less than with a sharp texture. This results in a homogeneous trapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…At the same time, scanning Hall probe microscopy (SHPM) provided additional information on the local distribution of the critical current density. Similar studies have been performed previously on pure YBCO layers grown on metallic templates [ 23 , 24 , 25 ].…”
Section: Introductionsupporting
confidence: 67%
“…At the same time, scanning Hall probe microscopy (SHPM) provided additional information on the local distribution of the critical current density. Similar studies have been performed previously on pure YBCO layers grown on metallic templates [ 23 , 24 , 25 ].…”
Section: Introductionsupporting
confidence: 67%
“…The spatial homogeneity of the superconducting properties was imaged using SHPM. The setup consists of a Hall effect sensor with a piezo-positioning system [8,9]. Magnetic field profiles were recorded in a He-gas flow cryostat where the temperature can be stabilized between 3 K and 300 K with a spatial resolution of 5 μm.…”
Section: Methodsmentioning
confidence: 99%
“…Two types of commercially available templates are typically used: a rolling-assisted biaxially textured substrate (RABiTS) made from NiW alloys and Hastelloy or stainless steel tapes with a textured buffer layer prepared by ion-beam assisted deposition or inclined substrate deposition. Various studies have shown that RABiTS tapes have large grains of usually more than 20 μm, which are transferred to the deposited REBCO layer [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, mainly YBa 2 Cu 3 O 6+ x (YBCO) and GdBa 2 Cu 3 O 6+ x (GdBCO) has managed to grow on these buffered metallic templates utilizing PLD for the large-scale coated conductor manufacturing . However, these nonsingle crystalline templates are extremely harsh growth environments for the films to be deposited due to the presence of the great number of grain boundaries, which are usually transferred on the film deposited on the top of it. This grain boundary transfer significantly diminishes the benefits of the HTS materials, such as liquid nitrogen cooling, as they limit the superconducting critial current more substantially in the high temperature range. The critical current, determined by the grain boundaries, has been observed to decrease linearly in zero field as the temperature is increased according to the superconductor–insulator–superconductor (SIS) model. More unfortunately, under applied magnetic fields the critical current is suppressed exponentially as a function of temperature, and in some cases the grain boundaries can even become weak links blocking the applied current completely. , …”
Section: Introductionmentioning
confidence: 99%